HUBUNGAN ANTARA PEMBELAJARAN BIPA DAN MINAT MAHASISWA DALAM BERKARIR SEBAGAI PENGAJAR BAHASA INDONESIA BAGI PENUTUR ASING - Taufik Kusuma Panjaitan; Amalia, Dhea; Amalia, Hoirina Pulungan; Hulu, Silfani; Amalia, Nadra Amalia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the increasing demand for Indonesian Language for Foreign Speakers (BIPA) instructors as the international recognition of the Indonesian language continues to grow. However, students’ interest in pursuing careers as BIPA instructors remains underexplored. This study aimed to determine the relationship between BIPA learning and students’ interest in pursuing careers as Indonesian language instructors for foreign speakers. A quantitative approach with a correlational design was employed. The participants consisted of 60 students from the Indonesian Language and Literature Education and Indonesian Literature Study Programs at Universitas Negeri Medan who had completed or were currently taking BIPA courses. Data were collected through a Likert-scale questionnaire and analyzed using descriptive statistics and Pearson Product Moment correlation with the assistance of SPSS. The results indicated that all questionnaire items were valid, with item correlation coefficients exceeding the critical value (0.254), and reliable, with a Cronbach’s Alpha coefficient of 0.758. Furthermore, the correlation analysis revealed a positive and significant relationship between BIPA learning and students’ career interest in becoming BIPA instructors (r = 0.753; p < 0.01). These findings suggest that better learning experiences in BIPA contribute to higher levels of career interest among students. Therefore, strengthening BIPA instruction in higher education is essential to support students’ career development and to meet the growing demand for qualified BIPA instructors.